Operational research within a Global Fund supported tuberculosis project in India: why, how and its contribution towards change in policy and practice. Issue 1 (1st January 2018) - Sagili, Karuna D; Satyanarayana, Srinath; Chadha, Sarabjit S; Wilson, Nevin C; Kumar, Ajay M V; Moonan, Patrick K; Oeltmann, John E; Chadha, Vineet K; Nagaraja, Sharath Burugina; Ghosh, Smita; Q Lo, Terrence; Volkmann, Tyson; et al.
ABSTRACT: Background : The Global Fund encourages operational research (OR) in all its grants; however very few reports describe this aspect. In India, Project Axshya was supported by a Global Fund grant to improve the reach and visibility of the government Tuberculosis (TB) services among marginalised and vulnerable communities. OR was incorporated to build research capacity of professionals working with the national TB programme and to generate evidence to inform policies and practices. Objectives : To describe how Project Axshya facilitated building OR capacity within the country, helped in addressing several TB control priority research questions, documented project activities and their outcomes, and influenced policy and practice. Methods : From September 2010 to September 2016, three key OR-related activities were implemented. First, practical output-oriented modular training courses were conducted (n = 3) to build research capacity of personnel involved in the TB programme, co-facilitated by The Union, in collaboration with the national TB programme, WHO country office and CDC, Atlanta. Second, two large-scale Knowledge, Attitude and Practice (KAP) surveys were conducted at baseline and mid-project to assess the changes pertaining to TB knowledge, attitudes and practices among the general population, TB patients and health care providers over the project period. Third, studies were conducted to describe the project's core activities and outcomes. Results : In the training courses, 44 participant teams were supported to develop research protocols on topics of national priority, resulting in 28 peer-reviewed scientific publications. The KAP surveys and description of project activities resulted in 14 peer-reviewed publications. Of the published papers at least 12 have influenced change in policy or practice. Conclusions : OR within a Global Fund supported TB project has resulted in building OR capacity, facilitating research in areas of national priority and influencing policy and practice. We believe this experience will provide guidance for undertaking OR in Global Fund projects.